The Moral Permissibility of Providing Medical Assistance in Dying in Canada: An Ethical Framework for Professional Practice - Christie, Timothy (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
Although medical assistance in dying (MAiD) is legally permitted in Canada under defined statutory conditions, this legal framework does not determine when it is morally permissible for a healthcare professional to provide MAiD. This paper explicitly examines the normative distinction between legal and ethical MAiD practice. It argues that the medically related eligibility criteria, such as incurability, irreversible decline, and intolerable suffering, do not function as objective medical criteria but instead presuppose and reinforce patient autonomy. As a result, MAiD assessments are often reduced to procedural confirmations of autonomy rather than substantive medical assessments. Thus, autonomy has become the de facto justification for the provision of MAiD, even though Canadian law does not regard autonomy alone as a sufficient condition. This paper examines the discretionary structure of MAiD practice and demonstrates that every decision to provide MAiD involves a normative judgment on the part of the healthcare professional. To guide that judgment, an ethics framework grounded in the fiduciary duties of healthcare professionals is proposed. Using the four core principles of healthcare ethics, this framework holds that it is morally permissible for a healthcare professional to provide MAiD only when: 1) the patient is autonomous, understood in terms of capacity, voluntariness, and informed consent; 2) the intervention satisfies the principles of beneficence and nonmaleficence; and 3) the request arises from a context of justice, in which a medical condition renders the patient unable to act on their autonomous wish to die without assistance.